Service Provider Selection For Project Logistics Operations With Fuzzy Analytic Hierarchy Process - Gökay Çiçekli; Yunus Kaymaz (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
The transportation of non-standard cargoes and related logistics operations are considered as a niche area that requires expertise. Logistics operations of non-standard cargoes must be carried out carefully in order to deliver the cargo on time and in undamaged conditions. Although a significant amount of literature has been published on service provider selection, there is no study in the field of project logistics. For this reason, it is necessary to investigate and determine the selection criteria for project logistics service providers. In the study, fuzzy analytical hierarchy process (FAHP) is used for project logistics service provider selection. The results are that for project logistics management, logistics service providers need to improve vehicle availability, cargo security, on-time delivery, etc. to become more competitive.